(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The evolution and impact of India’s regional political parties are the subject of this analysis. There has been a decentralisation of power in India’s democratic system since the country gained its independence, which is reflective of the country’s rich linguistic, cultural, and social variety. Factors such as economic inequality, the emergence of linguistic states, the importance of caste, class, and identity politics, and mobilisation around regional demands led to the emergence of regional parties. By establishing personal relationships with voters and taking up issues that national parties would ignore, these groups often serve as advocates for local concerns. The theoretical underpinnings, historical development, and effects of regional parties on India’s electoral process are all explored in this comprehensive study of regionalism. The democratisation of politics has been aided by regional parties, which have played key roles in coalition administrations and in defining national policy via both collaboration and rivalry with national parties. The study concludes that regional parties are necessary for fair representation under India’s federal system, highlighting the dual character of regionalism as a form of self-expression and a threat to central power.